Breast cancer in women older than those advised for mammographic screening in a public hospital in the Federal District - Belluco, Rosana Zabulon Feijó; Gomes, Carolina Gaze Gonçalves Fontenele; Belluco, Júllia Eduarda Feijó; Castro, Gabriel Piau de; Sanches, Caio Silva; Gomes, Igor Nathan Isidoro; Júnior, Carlúcio Pereira Leal; Belluco, Isabella Luísa Feijó (Mastology, 2026)
Objective: To evaluate the clinical-epidemiological profile of women diagnosed with breast cancer after 70 years of age in a public hospital in the Federal District. Methods: This is a cross-sectional, retrospective study that analyzed 169 women diagnosed with breast cancer at the Hospital Regional da Asa Norte, from January 2021 to July 2024. Data were assessed by using SAS 9.4 on the TrakCare platform, in absolute and percentage frequency. Of these, 32 met the inclusion criteria. Results: The patients’ mean age was 77.28, standard deviation ±4.51 years. The mean age at menarche was 11.76±1.48, and at menopause, 48.60±2.99 years. Regarding race, 20 (62%) women considered themselves brown, 9 (28%) white, and 2 (6%) black. The most prevalent comorbidity found was systemic arterial hypertension, in 22 (68%), followed by diabetes mellitus, in 13 (40%) patients. Regarding parity, the median was three pregnancies, with a quartile range of 3±2. Most of the women, 26 (81%), breastfed for at least six months. Family history was negative for the majority, 22 (68%), and only 5 (16%) underwent hormone replacement therapy. Only 10 (32%) reported smoking. The most prevalent histological type of cancer was invasive ductal carcinoma, found in 29 (91%) patients, and the molecular subtype was luminal A, present in 20 (62%) cases. Stage II was the most prevalent, 13 (40%), followed by stage III, 9 (28%). Surgical treatment was the most prevalent, with an equal distribution between conservative and radical surgery. Immediate breast reconstruction was performed in only 3 women (9.37%). Conclusion: Considering the aging of the Brazilian population and the increasing rates of breast cancer diagnoses in women over 70 years, it is concluded that mammographic screening in this age group should not be neglected, as it allows early diagnosis and curative treatment. Screening guidelines should not be limited to chronological age.